JOB COMPETENCY ASSESSMENT & TRAINING PROGRAM MAINTENANCE PADA PT. NPTI - Jonathan Susilo; Jani Rahardjo (Jurnal Titra, 2017)
PT. NPTI is a container operation terminal company. This research is aimed to improve employees’ performance. The main problem occurred in this company is the lack of Job Competency Assessment design. This situation makes the Human Resource Development cannot facilitate suitable training as well as career path for the employees. Their improvement is the fulfillment of clause 7.2 in ISO 9001:2015. In this research, improvement is given by constructing Job Competency Assessment in maintenance department so the gap of competency can be measured and it can be a guidance in determining appropriate training targets. Job Competency Assessment is also used to grade every employee’s competency which later will be a help to determine the employees’ career path.